A novel methodology for developing dense and porous implants on single generic optimized setting for excellent bio-mechanical characteristics - Mudassar Rehman; Yanen Wang; Kashif Ishfaq; Ray Tahir Mushtaq; Mohammed Alkahtani (Journal of Materials Research and Technology)
This work is performed to describe an optimization strategy to cope with the critical need for bio-implants with mechanical properties that closely resemble natural bone(cortical and trabecular), aiming to reduce stress-shielding effects and improve implant efficacy. An investigation was conducted on fracture mechanics, surface integrity, porosity, and cytotoxicity of bio-implants fabricated using Laser Powder Bed Fusion (L-PBF) technology. By varying laser energy density and applying post-processing multi-stage heat treatment (Annealing plus Aging), the bio-mechanical performance of dense and porous implants was optimized and tuned. The materials used include biomedical titanium alloys, which were selected for their superior biocompatibility and mechanical strength. This innovative approach enhanced bone healing, with 87% and 87.7% growth rates and a significant increase in compressive strength by approximately 84.62% post-treatment. These improvements are attributed to densification and elimination of microstructural defects, leading to increased biocompatibility and accelerated osseointegration, essential for the success of orthopedic implants.